2015
DOI: 10.1136/bmj.h2336
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners should embrace, not ignore, health apps

Abstract: medical student, Brian McMillan academic clinical fellow in primary care, Caroline Mitchell senior clinical lecturer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 1 publication
2
17
0
5
Order By: Relevance
“…35,36 Research has suggested that efficacy of apps is also dependent on long-term adherence to an app, otherwise the impact may be limited, and prompts where shown to increase effectiveness. 37 Far fewer than half of the investigated studies employed such strategies; eight studies prompted participant engagement by explicitly requesting input and only five studies sent intervention reminders based on adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Research has suggested that efficacy of apps is also dependent on long-term adherence to an app, otherwise the impact may be limited, and prompts where shown to increase effectiveness. 37 Far fewer than half of the investigated studies employed such strategies; eight studies prompted participant engagement by explicitly requesting input and only five studies sent intervention reminders based on adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The development of digital mental health services should be user-driven and solution-focused, including app developers, researchers and clinicians in the process. 37,4042 It is important to investigate app features and components, which make smartphone apps unique delivery modalities, such as context sensing, constant access and availability, high likelihood that prompts are received in daily life, and the combination possibilities with physiological assessments. The feature-driven approach could be helpful to understand working mechanisms of apps for mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The apps may be of particular benefit in primary care considering the heavy pressure on time and resources as well as the wide range of symptoms, diseases and patient groups involved [16]. The apps would seem ideal as support tools for physicians to use on specific patients in primary care, thus promoting health in the long term [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This is also a problem in assuring the quality and effectiveness of mMH applications. The unsuccessful experience of the NHS approved apps library is a good example of how the need for regulation is recognized but difficult to address [14,15]. Issues around the Samaritans Radar app, initially launched in 2014 and now withdrawn, show that designing an app to support mental health can cause unanticipated problems.…”
Section: Introductionmentioning
confidence: 99%